The relationship between critical life events, psycho-emotional health and life satisfaction among youths: coping mechanisms and emotional regulation - Marc, Gabriela; Mitrofan, Laurențiu; Vlad, Camelia-Iulia-Maria (Frontiers in Psychology, 2024)
Objective: Several studies in the specialized literature have reported that events such as the death of a loved one, job loss, divorce, illness, or retirement lead to an increase in the level of stress felt, and subsequently stress affects the person on several levels of life, such as: personal, relational, social, academic and at the same time sanogenic. The present paper explored the relationship between critical life events and psycho-emotional health among youths and the manner in which this relationship is mediated by the level of life satisfaction. Methods: The data was extracted using a sample of participants (between 20 and 40 years old) from several cities in Romania, who experienced one or more critical life events during the last year. Data organization and hypothesis testing were performed using IBM SPSS 23 and jamovi programs. For this purpose we used the simple regression analysis, Pearson correlation and mediation analysis. The scales used to conduct the research were: RS-14, SRRS, ERQ, CERQ, DASS-21 and SWLS. Results: The final sample of the study totaled 190 female and male Romanian participants aged between 20 and 40 (M = 24.45, SD = 5.27) who had experienced critical events during the last year, leading to psycho-emotional destabilization and a significantly lower level of life satisfaction. The prevalence of critical life events among these participants varied from one to five events (55.26%) and up to more than 16 critical events in the past year (2.63%). The presence of these events led to increased levels of stress, anxiety, or depression among participants. Furthermore, it appears that the presence of a high number of critical life events led to a decreased life satisfaction among participants, along with a greater tendency toward catastrophizing. Conclusion: Critical life events are increasingly frequent events in everyday life, and youth seems to be the period with the most changes. The research findings add to current findings about the practical implications that critical life events have on psycho-emotional health among youths. Therefore it appears to be a close relationship between critical life events, psycho-emotional health, and emotional regulation.